Modulation of immune responses using anti-CD30 antibody-drug conjugates - HEISE, RICHARD, A; GROGAN BRIAN M (2023)
Provided herein are anti-CD30 antibody-drug conjugates and methods of using the same to modulate an immune response in a subject. 本文提供抗CD30抗体-药物缀合物以及使用其调节受试者的免疫反应的方法。